A Comparison of Epileptogenic Effect of Status Epilepticus Treated With Diazepam, Midazolam, and Pentobarbital in the Mouse Pilocarpine Model of Epilepsy - Tong, Xiangzhen; Zhang, Zizhu; Zhu, Jianping; Li, Shuji; Qu, Shaogang; Qin, Bing; Guo, Yanwu; Chen, Rongqing (Frontiers in Neurology, 2022)
Status epilepticus (SE) is a medical emergency associated with acute severe systemic damage and high mortality. Moreover, symptomatic SE is one of the highest risk factors for epileptogenesis. While the antiepileptic drugs (AEDs) are chosen in favor of acute control of SE, the potential short-term and long-term effects of such AEDs have been ignored in clinics. In this study, we hypothesized that AEDs that are used to control acute SE might affect the feasibility for the chronic development of epileptogenesis after SE. Therefore, we sought to compare the epileptogenic effects of SE that are terminated by three AEDs, i.e., diazepam, midazolam, and pentobarbital, which are widely used as first-line anti-SE AEDs. For this purpose, we used a mouse model of SE induced by intraperitoneal (i.p.) injection of lithium chloride (LiCl)-pilocarpine. The pilocarpine-induced SE was terminated with diazepam, midazolam, or pentobarbital. Then we compared short-term and long-term effects of SE with different AED treatments by examining SE-associated mortality and behavioral spontaneous recurrent seizures (SRSs) and by using magnetic resonance imaging (MRI) and immunohistochemistry to evaluate pathological and cellular alterations of mice in the different treatment groups. We found that i.p. injections of diazepam (5 mg/kg), midazolam (10 mg/kg), and pentobarbital (37.5 mg/kg) were able to terminate acute pilocarpine-SE effectively, while pentobarbital treatment showed less neuroprotective action against lethality in the short phase following SE. Long-term evaluation following SE revealed that SE treated with midazolam had resulted in relatively less behavioral SRS, less hippocampal atrophy, and milder neuronal loss and gliosis. Our data revealed an obvious advantage of midazolam vs. diazepam or pentobarbital in protecting the brain from epileptogenesis. Therefore, if midazolam provides as strong action to quench SE as other AEDs in clinics, midazolam should be the first choice of anti-SE AEDs as it provides additional benefits against epileptogenesis.